2016
DOI: 10.1002/jcla.21949
|View full text |Cite
|
Sign up to set email alerts
|

Association of Serum Albumin Level and Mortality in Premature Infants

Abstract: Low serum albumin level within the first day of life is an independent predictor of mortality in preterm infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…In the light of our results, the levels of serum albumin in infants with AB are associated with the age, the weight for age percentile, and the inflammatory response. Accordingly, the positive correlation observed between the age and the serum albumin level has been previously recognized in neonates and small infants 24 , and malnutrition and inflammation are considered to play a major role in occurrence of hypoalbuminemia 9 . Although it has traditionally been linked to malnutrition and we observed that the weight for age percentile was independently associated to serum albumin levels, hypoalbuminemia is not considered a specific nutritional marker 9 .…”
Section: Discussionmentioning
confidence: 83%
“…In the light of our results, the levels of serum albumin in infants with AB are associated with the age, the weight for age percentile, and the inflammatory response. Accordingly, the positive correlation observed between the age and the serum albumin level has been previously recognized in neonates and small infants 24 , and malnutrition and inflammation are considered to play a major role in occurrence of hypoalbuminemia 9 . Although it has traditionally been linked to malnutrition and we observed that the weight for age percentile was independently associated to serum albumin levels, hypoalbuminemia is not considered a specific nutritional marker 9 .…”
Section: Discussionmentioning
confidence: 83%
“…Torer et al 8) investigated the association between serum albumin levels and mortality in premature infants. The prevalence of RDS, sepsis, and mortality was significantly higher in infants with serum albumin levels less than the 25th percentile.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, low serum albumin within 1 day of birth was associated with longer hospital stay, need for mechanical ventilation, and higher mortality 8,9) .…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…In addition to the significant univariate predictors of neonatal mortality such as GA [ 8 ], BW [ 8 ], Apgar score [ 8 ], initial [ 9 , 10 ], and lowest serum albumin levels [ 9 ], a variety of risk adjustment scores such as clinical risk index for babies II (CRIB II) score—which assesses 5 combined variables of sex, GA, BW, body temperature, and base excess—have been found to be good predictors for mortality in preterm infants before 32 weeks of gestation [ 11 ]. The relationship of these variables with mortality is in need of further investigation in ELBWIs near the viability limit.…”
Section: Introductionmentioning
confidence: 99%